Uterine PEComa initially misdiagnosed as a leiomyoma: Sonographic findings and review of the literature. Issue 5 (16th November 2020) - Fontana, Enrico; Savelli, Luca; Alletto, Andrea; Seracchioli, Renato
Abstract: Perivascular epithelioid cell neoplasms (PEComas) are rare mesenchymal tumors with malignant potential that arise from gynecological organs in up to 25% of cases. The lack of data regarding the preoperative US features of uterine PEComas is reflected by the frequent misdiagnosis with leiomyomas. We describe the sonographic appearance of a richly vascularized cervical PEComa mimicking a myoma and report the analysis of six additional cases in the literature with a description of their ultrasound features. Most cases involved a single lesion arising from the uterine cervix with a rapid growth pattern, regular margins, heterogeneous echogenicity, absence of shadowing, and moderate‐to‐rich vascularity.